Regional Accounting and Regional Development: Array - Ionescu, Romeo-Victor (The Journal of Accounting and Management, 2020)
The paper deals to the critical analysis of the social account model’s implementation on regional level. The analysis is realised on two steps. The first consists of literature review regarding Czamanski’s model. The second is focused on the analysis of the updated regional accounting model. The analysis covers the theoretical and practical approaches and points out the model’s strengths and weaknesses. Finally, the model can be used as a good investigation instrument in order to quantify the regional economic progress and welfare.